Creating an Effective Management System : Integrating Policy Deployment, TWI, and Kata - Graupp, Patrick, author; Steward, Skip, author; Parsons, Brad, author (Roca Raton, FL : CRC Press, Taylor & Francis Group, a Productivity Press Book, 2020)
"The decades of experience-based wisdom that Graupp, Steward and Parsons share will set you on a new path to a more joyful organization and the tangible results it will produce." Rich Sheridan, CEO, Menlo Innovations; author of Joy, Inc. and Chief Joy Officer "A fine book by skilled practitioners that integrates Kata and TWI, with Strategy Deployment in pursuit of an integrated management system. Well done, Skip, Brad and Patrick." Pascal Dennis, president, Lean Pathways Inc.; author of Lean Production Simplified, Andy & Me, Andy & Me and the Hospital, Getting the Right Things Done, and The Remedy "In this practical and engaging book, Patrick Graupp, Skip Steward, and Brad Parsons give a concise and extremely clear explanation of what systems thinking looks like in a healthcare setting. And they do so in a way that translates easily to any type of organization. Highly recommended!" Alan Robinson, co-author of Ideas Are Free and The Idea-Driven Organization.